Cowpea cultivars resistant to insect pests in world germplasm collection - Singh, S.R. (1977)
Cowpea, Vigna unguiculata (L . ) Walp. , is one of the most important grain legume crops in West Africa. It is cultivated over 4.8 million hectares in West Africa (Anon . 1974a) and is a major source of protein for t he people (Stanton 19 66). Cowpea yields fro m Africa are below 400 kg/ha. These low yields are attributed to poor crop husbandry and severe insect damage .